2015
DOI: 10.1111/cei.12458
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A induces interleukin-1β secretion from keratinocytes via the NACHT, LRR and PYD domains-containing protein 3 inflammasome

Abstract: SummaryInterleukin (IL)-1β is now emerging as a critical cytokine in the pathogenesis of T helper type 17 (Th17)-mediated skin diseases, including psoriasis. Psoriatic keratinocytes are a major source of IL-1β; however, the mechanisms triggering IL-1β processing remain unknown. Recently, an acute-phase protein serum amyloid A (SAA) has been identified as a danger signal that triggers inflammasome activation and IL-1β secretion. In this study, we detected increased SAA mRNA and protein expression in psoriatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 38 publications
(52 reference statements)
8
50
1
Order By: Relevance
“…Based on the Proteome Profiler ™ Array (R&D Systems, Minneapolis, MN, USA) results, we found that MSU selectively leads to the phosphorylation of two MAP kinase proteins: MAPK14/p38α and ERK1/2. This observation suggests that these two kinases are involved in the recognition of the MSU, and their activation leads to the upregulation of TLR2 , which occurs in several skin disorders for the recognition of microbial pathogens . This mechanism is similar to that reported for polycytidylic acid (Poly[I:C]), a TLR3 agonist that stimulates IL‐8/CXCL8 production in keratinocytes …”
Section: Discussionsupporting
confidence: 69%
“…Based on the Proteome Profiler ™ Array (R&D Systems, Minneapolis, MN, USA) results, we found that MSU selectively leads to the phosphorylation of two MAP kinase proteins: MAPK14/p38α and ERK1/2. This observation suggests that these two kinases are involved in the recognition of the MSU, and their activation leads to the upregulation of TLR2 , which occurs in several skin disorders for the recognition of microbial pathogens . This mechanism is similar to that reported for polycytidylic acid (Poly[I:C]), a TLR3 agonist that stimulates IL‐8/CXCL8 production in keratinocytes …”
Section: Discussionsupporting
confidence: 69%
“…Although the function of SAA1 is well described for liver and immune cells, any role in muscle is less well understood. For example, SAA1 can bind to several receptors, such as TLR2, TLR4, CD36, P2RX7, VIMP, and SCARB1, which are expressed on hepatocytes, keratinocytes, fibroblasts, and macrophages . Whether or not these receptors are involved in SAA1 signalling in myocytes was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the acute-phase response protein serum amyloid A1 (SAA1) was shown to be synthesized by and released from muscle of critically ill patients and septic mice [36]. SAA1 induces IL-1β expression [46] and secretion [47] and activates the Nlrp3 inflammasome in immune cells [46]. The Nlrp3 inflammasome is contained and active in C2C12 myocytes [48] .…”
Section: Discussionmentioning
confidence: 99%